UTILIZATION OF TELEMEDICINE AMONG UNDERGRADUATE STUDENTS AT THE FACULTY OF PUBLIC HEALTH, ANDALAS UNIVERSITY IN PADANG : UTILIZATION OF TELEMEDICINE - Setiawati, Santi; Fadhillah, M. Fadhillah; Aljutri, Aljutri; Sari, Melsi Pita; Dewi, Novi Putriana; Widoyo, Ratno (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Telemedicine is one of the health technology innovations that has rapidly developed during the COVID-19 pandemic. Due to physical limitations imposed by health protocols, telemedicine has become an essential alternative to maintain the continuity of healthcare services. This study aims to identify the factors influencing the use of telemedicine services and to examine the relationship between student characteristics and the utilization of telemedicine. Methods: A cross-sectional survey method was used, targeting students who use teleconsultation applications, with a total of 105 respondents in 2025. The sampling technique used was proportionate random sampling to obtain a representative sample from each department based on population size. Variables examined in this study included respondent characteristics such as gender, academic program, menstrual status, telemedicine usage, and types of services used. Results: The results showed that 15.2% of students actively used telemedicine services, while 84.4% had never used them. Of those who used telemedicine, 81.25% used it for registration services and 75% for counseling. Active users were mostly female public health students who had experienced menstruation. Statistical tests showed no significant relationship between gender and telemedicine use (p-value = 0.163), nor between study program and service use (p-value = 0.195). However, there was a significant relationship between menstrual status and telemedicine use (p-value = 0.001). Conclusion: This study provides important input for the development of sustainable digital health services in Indonesia, especially among university students.